SH2 domain containing leukocyte phosphoprotein of 76-kDa (SLP-76) feedback regulation of ZAP-70 microclustering - Liu, Hebin (National Academy of Sciences, 2010)
T cell receptor (TCR) signaling involves CD4/CD8-p56lck recruitment of ZAP-70 to the TCR receptor, ZAP-70 phosphorylation of LAT that is followed by LAT recruitment of the GADS-SLP-76 complex. Back regulation of ZAP-70 by SLP-76 has not been documented. In this paper, we show that anti-CD3 induced ZAP-70 cluster formation is significantly reduced in the absence of SLP-76 (i.e., J14 cells) and in the presence of a mutant of SLP-76 (4KE) in Jurkat and primary T cells. Both the number of cells with clusters and the number of clusters per cell were reduced. This effect was not mediated by SLP-76 SH2 domain binding to ZAP-70 because SLP-76 failed to precipitate ZAP-70 and an inactivating SH2 domain mutation (i.e., R448L) on SLP-76 4KE did not reverse the inhibition of ZAP-70 clustering. Mutation of R448 on WT SLP-76 still supported ZAP-70 clustering. Intriguingly, by contrast, LAT clustering occurred normally in the absence of SLP-76, or the presence of 4KE SLP-76 indicating that this transmembrane adaptor can operate independently of ZAP-70-GADS-SLP-76. Our findings reconfigure the TCR signaling pathway by showing SLP-76 back-regulation of ZAP-70, an event that could ensure that signaling components are in balance for optimal T cell activation.